Studi Retrospektif Pola Maloklusi dan Distribusi Geografis Pasien Ortodonsia di RSUD Tarakan Jakarta - Dhinintya Hyta; Riza Rosalina (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Malocclusion is a high-burden oral health problem that affects orofacial function and quality of life, with a global prevalence of approximately 56% among children and adolescents and a substantial burden in Asia, including school-aged populations in Indonesia. The increasing demand for orthodontic treatment in Jakarta has not been fully supported by local epidemiological data from provincial referral hospitals. This study aimed to determine the pattern of malocclusion based on Angle classification, its association with demographic characteristics, types of orthodontic treatment, and the geographic distribution of orthodontic patients at RSUD Tarakan Jakarta. This retrospective descriptive observational study analyzed medical records from September 1 to December 31, 2025, involving 47 samples out of 103 eligible patients diagnosed with malocclusion according to Angle classification, with data presented using frequencies and percentages. The results showed that most patients were female (65.96%) and aged 20–40 years (51.06%), with Class I malocclusion being the most common diagnosis (44.68%), followed by Class II division 1 (31.91%), Class II division 2 (17.02%), and Class III (6.38%), while crowding and spacing were the most frequent accompanying dental positional anomalies. Most patients underwent non-extraction treatment (68.09%) and were distributed across 28 districts, predominantly from South and Central Jakarta. These findings highlight the role of RSUD Tarakan as a regional orthodontic referral hospital and emphasize the importance of local epidemiological data for service planning and preventive-promotive programs in urban areas.